2020
DOI: 10.1186/s12943-020-1145-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Exosome-mediated lncRNA AFAP1-AS1 promotes trastuzumab resistance through binding with AUF1 and activating ERBB2 translation

Abstract: Background: Although trastuzumab provides significant clinical benefit for HER2-positive breast cancers, responses are limited by the emergence of resistance. Recent evidence suggests that long noncoding RNAs (lncRNAs) play important roles in tumorigenesis and chemoresistance. However, the regulatory mechanism of lncRNAs in trastuzumab resistance is not well established to date. In this research, we identified the differentially expressed lncRNA and investigated its regulatory role in trastuzumab resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
126
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 45 publications
0
126
0
Order By: Relevance
“…According to previous studies, abnormally high expression of lncRNA may be induced by transcription activators, stress, DNA methylation, and exosomes [47][48][49][50][51]. For example, the tumor suppressor gene p53 can transcriptionally activate lncRNA Pvt1b [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, abnormally high expression of lncRNA may be induced by transcription activators, stress, DNA methylation, and exosomes [47][48][49][50][51]. For example, the tumor suppressor gene p53 can transcriptionally activate lncRNA Pvt1b [47].…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of lncRNA SNHG12, mediated by DNA methylation, thereby activating and increasing temozolomide resistance in glioblastoma [50]. Exosome-mediated lncRNA AFAP1-AS1 activates ERBB2 translation [51]. However, few studies have explored the mechanism underlying the abnormally low expression of lncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, the effects of exosomal lncRNA in drug resistance were also demonstrated. For instance, exosome-mediated transfer of AFAP1-AS1 induced trastuzumab resistance in breast cancer via the interaction with AUF1 and the activation of ERBB2 translation [26]. Intercellular transfer of lncRNA H19 promoted doxorubicin resistance in breast cancer [27].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, emerging evidence has indicated that exosomes regulate malignancyby transferring multiple classes of cargo molecules to recipient cells to mediateintercellular communication, including lncRNAs. Exosomal lncRNAs participate in tumor formation,proliferation, metastasis and chemotherapy resistance by regulating oncogenes ortumor suppressor genes [9,36,37]. However, communication in BC cells withdifferent drug response via exosomes is obscured.…”
Section: Discussionmentioning
confidence: 99%